Fall and Winter Movements of Bowhead Whales (Balaena mysticetus) in the Chukchi Sea and Within a Potential Petroleum Development Area - Quakenbush, Lori T.; Citta, John J.; George, John C.; Small, Robert J.; Heide-Jørgensen, Mads Peter (ARCTIC, 2010)
Working with subsistence whale hunters, we tagged 19 mostly immature bowhead whales (Balaena mysticetus) with satellite-linked transmitters between May 2006 and September 2008 and documented their movements in the Chukchi Sea from late August through December. From Point Barrow, Alaska, most whales moved west through the Chukchi Sea between 71˚ and 74˚ N latitude; nine whales crossed in six to nine days. Three whales returned to Point Barrow for 13 to 33 days, two after traveling 300 km west and one after traveling ~725 km west to Wrangel Island, Russia; two then crossed the Chukchi Sea again while the other was the only whale to travel south along the Alaskan side of the Chukchi Sea. Seven whales spent from one to 21 days near Wrangel Island before moving south to northern Chukotka. Whales spent an average of 59 days following the Chukotka coast southeastward. Kernel density analysis identified Point Barrow, Wrangel Island, and the northern coast of Chukotka as areas of greater use by bowhead whales that might be important for feeding. All whales traveled through a potential petroleum development area at least once. Most whales crossed the development area in less than a week; however, one whale remained there for 30 days. De concert avec les pêcheurs de baleines de subsistance, nous avons apposé des transmetteurs satellitaires sur 19 baleines boréales (Balaena mysticetus) pour la plupart immatures entre les mois de mai 2006 et septembre 2008, puis nous avons tenu compte de leurs mouvements dans la mer de Tchoukotka de la fin août jusqu'au mois de décembre. À partir de Point Barrow, en Alaska, la plupart des baleines se déplaçaient vers l'ouest dans la mer de Tchoukotka entre 71˚ et 74˚ N de latitude; neuf baleines ont fait la traversée en six à neuf jours. Trois baleines ont regagné Point Barrow pendant 13 à 33 jours, dont deux après avoir franchi 300 kilomètres en direction ouest et une après avoir franchi environ 725 kilomètres en direction ouest jusqu'à l'île Wrangel, en Russie; ensuite, deux baleines ont ...